Heterologous expression of mating-type genes in filamentous fungi. - Arnaise, S (1993)
Podospora anserina and Neurospora crassa, two filamentous heterothallic ascomycetes, have a single mating-type locus with two alternate forms called mat+ and mat- and A and a, respectively. Mating type controls entry into the sexual cycle, events subsequent to fertilization, and, in N. crassa, prevents the formation of mixed mating-type heterokaryons. The mating types of these two organisms display similarity in their DNA structure and in the encoded polypeptides involved in fertilization. Here we show that this molecular similarity reflects a functional homology with respect to mating identity. Transformation experiments show that the N. crassa mating-type genes can provide the fertilization functions in P. anserina strains devoid of mating specificity as well as in mat+ and mat- strains. Reciprocally, the introduction of P. anserina mating-type genes confers mating activity in N. crassa. Functional identity between the mating types is not observed for vegetative incompatibility or for post-fertilization events such as meiosis and ascosporogenesis.